Bricolage as conceptual tool for understanding access to healthcare in superdiverse populations - Phillimore, J.; Bradby, H.; Knecht, M.; Padilla, B.; Pemberton, S. (Social Theory and Health, 2019)
This paper applies, for the first time, the concept of bricolage to understand the experiences of superdiverse urban populations and their practices of improvisation in accessing health services across healthcare ecosystems. By adopting the concept of healthcare bricolage and an ecosystem approach, we render visible the agency of individuals as they creatively mobilise, utilise, and re-use resources in the face of constraints on access to healthcare services. Such resources include multiple knowledges, ideas, materials, and networks. The concept of bricolage is particularly useful given that superdiverse populations are by definition heterogeneous, multilingual and transnational, and frequently in localities characterised as ‘resource-poor’, in which bricolage may be necessary to overcome such constraints, and where mainstream healthcare providers have limited understanding of the challenges that populations experience in accessing services. The ‘politics of bricolage’ as neoliberal strategies of self-empowerment legitimising the withdrawal of the welfare state are critically discussed. Conflicting aspects of bricolage are made explicit in setting out tactics of relevance to researching the practices of bricolage.